LIPID-LOWERING AND PLEIOTROPIC EFFECTS OF ATORVASTATIN IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - SVETLANA A. Smakotina; SVETLANA A. Berns; EVGENIYA B. Gerasimova (Фундаментальная и клиническая медицина)
Aim. To investigate how 6-month atorvastatin treatment affects serum lipid profile, pulmonary function, cytokine profile, and endothelial function in patients with chronic obstructive pulmonary disease (COPD) but without cardiovascular disease (CVD). Materials and Methods. We recruited 83 consecutive male smokers with COPD but without CVD who was prescribed with bronchodilator therapy. Patients were stratified into the two groups: with (n = 42) and without (n = 41) atorvastatin treatment. At the baseline and upon 6 months of atorvastatin (20 mg/day) treatment, we performed spirometry, body plethysmography, brachial artery reactive hyperemia test, lipid profiling, and measurements of serum interleukin (IL)-6, IL-8, tumor necrosis factor-α (TNF-α), and endothelin-1 (ET-1). Cardiovascular risk was evaluated in accordance with the SCORE scale. Results. Upon 6-month treatment with atorvastatin, all patients achieved the target level of low-density lipoprotein cholesterol. Furthermore, treatment significantly decreased cardiovascular risk, improved lung diffusion capacity, increased forced expiration volume in 1 second, enhanced endothelium-dependent dilation, and reduced the level of ET-1 and pro-inflammatory cytokines. Conclusions. 6-month administration of atorvastatin in patients with COPD but without CVD improves serum lipid profile, reduces concentration of pro-inflammatory cytokines, and enhances both pulmonary and endothelial function.